The Statutes at Large of Pennsylvania from 1682 to 1801, at 108, ch. 388, § 1 (Vol. 5, 1898) - (:unkn) unknown (General Publisher, 1750)
That if any persons or persons whatsoever, within any county town, or within any other town or borough, in this province, already built and settled, or hereafter to be built and settled . .. shall fire any gun or other fire-arm, or shall make or cause to be made, or sell or utter, or offer or expose for sale, any squibs, rockets or other fire-works, within any of the said towns or boroughs without the Governor's special license for the same, every such person or persons, so offending shall be subject to the like penalties and forfeitures, and to be recovered in like manner, as in and by an act, passed in the eighth year of the reign of King George the first, entitled, "An act for preventing accidents that may happen by fire, are directed to be levied and recovered."
--
Keywords: DISCHARGE